IMMEDIATE AND LONG-TERM RESULTS OF COMPLEX TRADITIONAL TREATMENT OF PATIENTS WITH PANCREATIC NECROSIS COMPLICATED BY SEPSIS - Khamdamov, B.Z.; Musoev, T.Y.; Khaydarov, F.N.; Ganiyev, A.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. An analysis of the literature over the past 10 years has shown that there are more and more supporters of conservative therapy of pancreatic necrosis with active wait-and-see tactics. To improve the effectiveness of treatment and diagnostic tactics, proponents of this approach offer complexes of algorithms. Material. A retrospective cohort study of the results of a comprehensive examination and treatment of 97 patients with pancreatic necrosis was conducted. All patients were treated and examined in the Bukhara regional branch of the Republican Scientific and Practical Medical Center for Emergency Medical Care from 2013 to 2017. Conclusion. And the results of traditional methods of treatment of pancreatic necrosis complicated by sepsis showed the presence of a high level of complications of the disease (38.1%) and mortality (30.9%), due to the lack of objective criteria for predicting the development of pancreatogenic sepsis and multiple organ dysfunction syndrome, which requires detailed studies of the pathogenetic mechanisms of this formidable disease.